Addition of intrarectal local analgesia to periprostatic nerve block improves pain control for transrectal ultrasonography‐guided prostate biopsy: A systematic review and meta‐analysis. (21st August 2014) - Wang, Jue; Wang, Lei; Du, Yiqing; He, Dalin; Chen, Xingfa; Li, Lei; Nan, Xunyi; Fan, Jinhai
<x xml:space="preserve">Abstract</x> Objectives To evaluate the efficacy and safety of combined intrarectal local analgesia and periprostatic nerve block versus periprostatic nerve block alone for pain control during transrectal ultrasound‐guided prostate biopsy. Methods We comprehensively searched PubMed, Embase and the Cochrane Library trials. Studies comparing the two techniques were identified and pooled for cumulative analysis. The outcome measurements included visual pain scales of three consecutive procedures of transrectal ultrasound‐guided prostate biopsy, as well as short‐term postoperative complication rates. Results There were 18 studies that were finally eligible for the quantitative analysis involving 2076 participants. Combined modalities significantly reduced the pain associated with probe manipulation (weighted mean difference −2.06, 95% confidence interval −2.77 to −1.35, P < 0.001), anesthesia infiltration (weighted mean difference −1.45, 95% confidence interval −2.20 to −0.70, P < 0.001) and needle biopsy (weighted mean difference −0.55, 95% confidence interval −0.76 to −0.34, P < 0.001). Subgroup analyses assessing different local analgesics showed that local anesthetics are generally more effective than myorelaxant and non‐steroidal anti‐inflammatory drugs. Lidocaine‐prilocaine cream proved the most effective in pain control regardless of the origin of pain. No significant difference of short‐term postoperative complications (fever, dysuria, acute urinary retention, hematuria, hematospermia and rectal bleeding) was found between the two techniques. The only side‐effect associated with local analgesics was headache reported in studies using glyceryl trinitrate ointment. Conclusions Combined modalities show better analgesic efficacy than periprostatic nerve block alone for transrectal ultrasound‐guided prostate biopsy without increased morbidities. Among the various local analgesics, lidocaine‐prilocaine cream seems to offer the best overall efficacy.